Sustainable engineering labs - A Portuguese perspective - Caetano, Nídia (2019)
Strategies to reduce emissions responsible for greenhouse effect, and contributing to economy decarbonisation, should focus on using renewable energy, increasing energy efficiency both at production, distribution and consumption (equipment efficiency), sustainable mobility, urban renewal and rehabilitation and behavioural changes. Considering that man spend a significant part of their lives inside buildings that represent a significant share of energy consumption, buildings turn out to be an attractive area to invest efforts, aiming to improve efficiency, as recommended in the European Commission reports. However, despite the goals outlined in the Energy Performance of Buildings Directive, there are difficulties in the projection of new buildings that can be classified as nearly Zero Energy Buildings (nZEB). These include legal and financial obstacles, as insufficient formation of professionals (such as architects, engineers and consultants) able to tackle the challenges. This paper aims to point strategies that can contribute to the creation of a nearly zero energy laboratory in a university environment, that works as a tool for raising awareness about nZEB while improving the future engineering professionals’ skills towards team work and knowledge sharing – a living lab.